Performance evaluation of montmorillonite and modified montmorillonite by polyethyleneimine in removing arsenic from water resources. Issue 45 (25th September 2016) - Nadali, Azam; Khoobi, Mehdi; Nabizadeh, Ramin; Naseri, Simin; Mahvi, Amir Hossein
Abstract: Arsenic, known as a pollutant, mostly found in ground water resources, has become a major problem in the most of underdeveloped and developing countries around the world. More than 140 million of people around the world, especially those who reside in South America and south-east of Asia, are gravely at risk of being exposed to arsenic pollution. In this study, the performance of montmorillonite (MMT) and modified montmorillonite by polyethyleneimine (MMT@PEI) in removing arsenic from water resources was evaluated and compared with each other. Response surface methodology used as experimental procedures and interaction of four variables, namely, detention time, pH, initial arsenic concentration, and the adsorbent concentration on the arsenic ion removal were conducted. It is noteworthy that all chemical experiments conducted in this study are in accordance with "Standard Methods for Water and Wastewater Experiments." Also, XRD analysis was performed to determine the characteristics of the adsorbent. Based on the results, maximum percentage of fluoride removal efficiencies by applying montmorillonite ( R 2 = 0.95) and modified montmorillonite ( R 2 = 0.97) were 45 and 96%, respectively.